2021
DOI: 10.1007/s00431-021-04238-1
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric obstructive sleep-disordered breathing is associated with arterial stiffness

Abstract: The association between obstructive sleep-disordered breathing (oSDB) and arterial stiffness, an independent predictor of cardiovascular outcomes, is not well established in children. This study compared cardiovascular parameters between healthy and oSDB children and aimed to identify predictors of arterial stiffness indices in children with oSDB. MethodsCross-sectional study realized in a tertiary hospital from June 2018 to January 2020. 48 children (3 to 10 years old) with clinical diagnosis of oSDB and indi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…This is justi ed because the increase in AP would be due to an increase in the magnitude and not in the velocity of the re ection wave. Thus, several studies have shown changes in AIx@75 without signi cant changes in PWV in children, which corroborates our ndings [13,14,18,20]. The inverse of this process occurs in older individuals, where PWV increases and AIx changes slightly, which suggests that the increase in AP would be driven by an earlier return of the re ected wave and a less compliant aorta rather than predominant changes in the magnitude of wave re ection [12,40].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This is justi ed because the increase in AP would be due to an increase in the magnitude and not in the velocity of the re ection wave. Thus, several studies have shown changes in AIx@75 without signi cant changes in PWV in children, which corroborates our ndings [13,14,18,20]. The inverse of this process occurs in older individuals, where PWV increases and AIx changes slightly, which suggests that the increase in AP would be driven by an earlier return of the re ected wave and a less compliant aorta rather than predominant changes in the magnitude of wave re ection [12,40].…”
Section: Discussionsupporting
confidence: 90%
“…Santos et al found no association between quality of life in children and adolescents and AIx@75 [13]. In contrast, Rossi-Monteiro et al showed an association between worsening quality of life in children aged 3 to 10 years with obstructive sleep-disordered breathing and an increase in PWV [14]. For the adult population, however, it has already been established that worsening in quality of life is associated with an increase in arterial stiffness rates [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, we did not collect family history data for cardiovascular disease and dietary habits; and fourth, we did not exclude participants with a history of obstructive sleep-disorder breathing. We recently demonstrated that children with obstructive sleep-disorder breathing have increased arterial stiffness, evidenced by the increase in AIx@75 [ 33 ]. Herein, we show that the factors which present a greater chance of reducing PPA in the univariate logistic regression are related to the reflection wave, reflection coefficient, augmentation pressure and AIx@75.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular parameters were evaluated according to previous studies by our group [ 15 , 23 ]. Arterial stiffness (AS) was noninvasively estimated by measuring pulse wave velocity (PWV) and frequency-corrected augmentation index of 75 bpm (AIx@75) using the Mobil-O-Graph® device (IEM Germany - The Pulse Wave Analysis Monitor, version 4.8, Vienna, Austria).…”
Section: Methodsmentioning
confidence: 99%